Pregabalin and hyperbaric oxygen therapy on pain thresholds and anxio-depressive behaviors in a preclinical fibromyalgia pain model - Argenbright, Cassie M.; Bland, Michelle K.; Michener, Sydney L.; Wilson, Judy R.; Fuchs, Perry N. (Frontiers in Pain Research, 2023)
Fibromyalgia (FM) is a chronic, widespread pain disorder generally of a non-inflammatory nature with many known affective and cognitive comorbidities. There is promise in the implementation of hyperbaric oxygen therapy (HBO2) for alleviating FM pain and comorbidities, despite no work investigating the efficacy of this treatment in prominent preclinical FM models. This project aimed to investigate the affective components, specifically anhedonia and anxiety, associated with an acidic saline model of FM in rats. We investigated the acidic saline model’s ability to produce the sensory component of FM through reduced mechanical thresholds, as well as anxiety-like and avoidance behaviors through measures of open field and place escape/avoidance. We further investigated the use of pregabalin, a known FM therapeutic agent, in reducing negative sensory and affective measures within the model. Results revealed insignificant between-group differences for measures of anxiety, despite animals in the FM condition showing significantly reduced mechanical thresholds. Results further revealed that the acidic saline model was effective in increasing place escape/avoidance behavior among animals in the FM condition, with pregabalin reducing avoidance behaviors. In addition, we investigated the role of HBO2 (two 60-minute treatments at 2.0 ATA (atmospheres absolute)) in alleviating FM-like pain, anxiety, and anhedonia in the acidic saline model, utilizing mechanical paw withdrawal thresholds, open field, and sucrose preference measures. Results revealed that the acidic saline model produced reduced thresholds indicative of FM-like pain. Data did not provide support for the presence of anxio-depressive comorbidities associated with the FM model. HBO2 treatment did not significantly increase mechanical thresholds as expected. Future studies should seek to investigate the experimental circumstances within which the acidic saline model produces negative affect alongside hyperalgesia in order to contribute to the development of a multidimensional FM treatment methodology.